Interpretation Of Secondary Characters In A Literary Work (Texas Journal of Philology, Culture and History, 2025)
This article analyzes the concept of a character in a literary work, specifically focusing on the artisticfunctional roles of secondary characters. The main goal of the research is to identify and scientifically present the roles of secondary characters in plot dynamics, revealing the nature of the main protagonist and depicting the social environment in examples from Uzbek literature. The research employs literary theory, the concept of character, and methods of artistic text analysis. Practical analysis is carried out using Khurshid Dustmuhammad’s stories 'Iffat' and 'The Trick of Investigator Yoqub', revealing the functional roles of secondary characters in plot and idea development. The results show that secondary characters play an important role in plot structure, psychological disclosure of the protagonist’s character, and artistic expression of the social environment. It concludes that studying such characters scientifically helps fully understand the ideological-artistic system of a literary work.